MODEL OPTIMIZATION OF PERISHABLE GOODS TRANSPORTATION DISTRIBUTION (CASE STUDY: DISTRIBUTION OF STRAWBERRIES VIA AIR CARGO) - Budiarto, Samsul
The aim of this study is to build an optimization model of transport distribution that focuses on the transport of perishable goods, from product sources to air cargo warehouses at the airports, the high damage of perishable goods caused by improper handling has a significant impact on losses, research on optimizing the security of the perishable goods is currently developing, yet still cannot answer the problems that occur in agricultural products that will be distributed via air cargo lines. This research contributes to filling the gap from the perspective of supply chain network design from perishable products and the proposed model integrates strategic and tactical decisions and aims to minimize product delivery time and cost. The supply chain network investigates the involvement of 6 entities namely farmers, collectors, bookies, agents, regulated agents and airport cargo warehouses, realistic issues are also considered in terms of modes and distribution routes between entities. The solution approach is based on the optimization’s method by using the Excel Solver Software and network design models to determine the location and identification of transportation routes. To validate the model built on the factual conditions in the field is done by applying the methodology proposed for a real case study from strawberries’s supply chain. The results of this study are The built model is able to answer the problem of optimizing the transportation distribution of strawberries. and calculation of the cost and duration of transportation using the model built is better than the current system. With an efficiency of 37.5% for transportation costs and 23% for delivery time and then this research shows the design of a perishable product supply chain, trade-offs must be made between transportation costs, delivery times and product damage limits. This research only considers aspects of facilities and infrastructure, without considering institutional aspects, so to further refine in subsequent studies it can also involve aspects of institutional roles and functions of the distribution and transportation system of perishable products (strawberries) in Ciwidey.